Teaching Students How to Tame the Warrant with the Toulmin Model in EFL/ESL Settings - Sherma, Amar Bahadur (Journal of Academic Writing, 2024)
This teaching practice paper deals with some practical ideas of teaching the concept of ‘warrant’ in Toulmin’s mode of argumentation within EFL/ESL settings. While most students are familiar with making claims and providing evidence to support them, they may not understand the role of the warrant in connecting claims and reasons. Therefore, there is a strong need for teaching students how warrant plays a key role in argumentative writing. This teaching practice paper aims at bridging the gulf between some writing theories and useful examples to dissect the complexities of teaching warrant in writing classes.